THE EFFECTIVENESS OF THE APPLICATION OF THE LAW IN WASTE MANAGEMENT POLICIES IN SINDANGBARANG VILLAGE - Yuna Mumpuni Rahayu; Shinta Dwi Permatasari; Nuni Khoirinnisa Hudaya Taher; Ratna Sari; Atha Salsabila Zulfa (Jurnal Abdisci, 2025)
Abstract Background. The waste problem at the village level is still a serious challenge, especially in areas with minimal infrastructure and public awareness, such as Sindangbarang Village. Although policies and regulations have been implemented through Kuningan Regent Regulation Number 46 of 2018, the effectiveness of law enforcement in waste management is still not optimal. Aims. This study aims to analyze the extent to which implementing the law can be an effective solution for waste management in the village. Methods. The research method used is qualitative with a descriptive approach and data triangulation techniques through observation, interviews, and documentation. Result. The study's results indicate that various obstacles, such as the lack of waste management facilities, minimal community education, and limited budget and human resources, are the main obstacles to the policy's effectiveness. Conclusion. Strict law enforcement, ongoing education, and collaboration between institutions are needed to increase community participation and support sustainable waste management. Implementation. These findings emphasize the importance of strengthening regulations and the community's active role in creating a clean and healthy village environment.